An Assembly of Anomalous Extensor Tendons of the Hand – Anatomical Description and Clinical Relevance - Vandana Mehta (Acta Medica, 2009)
Innumerable descriptions about variations in the pattern of extensor tendons are recorded in the literature. The dorsum of the hand in an adult male cadaver revealed an unusual pattern of extensor arrangement during a gross anatomical practical session. The extensor digitorum, extensor indicis and extensor digiti minimi tendons displayed a variant pattern. Extensor digitorum contributed tendons only to the middle and ring fingers, with junctura tendinum present between the extensor digitorum for the ring finger and extensor digiti minimi. Interestingly, an accessory muscle was observed arising from the common extensor origin passing to the index finger, in addition to the usual extensor indicis. The origin and insertion of extensor digiti minimi was as usual with an accessory slip contributed from the extensor carpi ulnaris to the proximal phalanx of the fifth finger. The plethora of variations in this region is of paramount importance for the reconstructive surgeon, who may utilize the accessory tendons to restore functional capacity of the fingers.